2000
DOI: 10.1098/rspb.2000.1110
|View full text |Cite
|
Sign up to set email alerts
|

Macrofilaricidal activity of tetracycline against the filarial nematode Onchocerca ochengi : elimination of Wolbachia precedes worm death and suggests a dependent relationship

Abstract: Filarial nematodes are important and widespread parasites of animals and humans. We have been using the African bovine parasite Onchocerca ochengi as a chemotherapeutic model for O. volvulus, the causal organism of`river blindness' in humans, for which there is no safe and e¡ective drug lethal to adult worms. Here we report that the antibiotic, oxytetracycline is macro¢laricidal against O. ochengi. In a controlled trial in Cameroon, all adult worms (as well as micro¢lariae) were killed, and O. ochengi intrader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
143
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 21 publications
(36 reference statements)
4
143
3
1
Order By: Relevance
“…It is closely related to the human pathogen O. volvulus on the basis of 16S ribosomal RNA analyses (18) and shares the same vector, Simulium damnosum (63)(64)(65)(66). Wolbachia bacteria belonging to two distinct phylogenetic clades, those that are endosymbionts of the filarial nematode O. ochengi and those from a mosquito cell line Aedes albopictus, induced remarkably similar innate immune receptors and intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is closely related to the human pathogen O. volvulus on the basis of 16S ribosomal RNA analyses (18) and shares the same vector, Simulium damnosum (63)(64)(65)(66). Wolbachia bacteria belonging to two distinct phylogenetic clades, those that are endosymbionts of the filarial nematode O. ochengi and those from a mosquito cell line Aedes albopictus, induced remarkably similar innate immune receptors and intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In filarial worms, Wolbachia bacteria are concentrated in intracytoplasmic vacuoles of hypodermal lateral cords and female reproductive organs and are also detectable in oocytes and microfilaria, reflecting matrilinear inheritance (16). Nematode reproduction, molting, and survival dependent on the endosymbiont as prolonged exposure to antibiotics targeting Wolbachia result in decreased fecundity, impaired molting, and even worm death in vitro as well as in animal and human infections (17)(18)(19)(20). Results of studies of filaria-infected individuals are consistent with the hypothesis that Wolbachia contribute to the pathogenesis of filarial disease.…”
mentioning
confidence: 99%
“…Previous antibiotic curing experiments showed that the Wolbachia strains wBm, wOo, and wCle are essential for their hosts B. malayi, O. ochengi, and C. lectularius, respectively (9,26,27). Although wCle was shown to provide B vitamins to its bedbug host (Fig.…”
Section: Contrasting Mutualistic Wolbachia Genomes Associated With Bementioning
confidence: 99%
“…The success of Wolbachia can be attributed in large part to its ability to manipulate the reproduction of its host to promote infection spread into the host population. Wolbachia infections provide multiple examples of mechanisms that promote infection spread, ranging along the continuum from mutualism (Hoerauf et al, 1999;Langworthy et al, 2000) to reproductive parasitism. Examples of the latter include cytoplasmic incompatibility (Hoffmann and Turelli, 1997), male killing (Hurst et al, 1999), parthenogenesis (Stouthamer et al, 1993), and feminization (Rousset et al, 1992).…”
Section: Introductionmentioning
confidence: 99%